EFFECT OF BIOXCELL AND TRIS CITRIC EGG YOLK EXTENDER ON POST THAW SEMEN QUALITY AND IN VIVO FERTILITY IN CROSS BRED JERSEY BULL - BEURA, D; MISHRA, P C; DAS, P; MOHANTY, D N; BARIK, A K; BISWAL, S S (The Indian Journal of Animal Reproduction, 2023)
Present investigation was carried out to compare the commercially available extender Bioxcell® with tris citric egg yolk (TEYG) extender for post thaw quality and in-vivo fertility of jersey Red Sindhi cross bred bulls (CBJ). Twenty four ejaculates of semen samples were collected from four fertile CBJ bulls (5-6 years) by artificial vagina maintained at 41 °C.Qualifying ejaculates (>60% motility) from each bull were divided into two aliquots and diluted with TEYG or Bioxcell®extender. Diluted semen was cooled, equilibrated at 4°C for 4hrs and filled in 0.5ml straws. Straws were cryopreserved in liquid nitrogen for 24 hrs. and then thawed at 37°C for 30 seconds to assess post thaw motility (PTM), livability (PTL), plasma membrane integrity (HOSr), and percent intact acrosome (PIA). For comparison of in vivo fertility cows were inseminated under field condition and fertility rate was calculated on conception rate (CR) basis. The PTM, PTL, HOSr and PIA were found to be 51.05 ± 0.25 and 51.82 ± .26, 56.47 ± 0.41 and 56.46 ± 0.42, 67.94 ± 0.46 and 67.99 ± 0.45 and 69.53 ± 0.52 and 69.55± 0.52 in TEYG and Bioxcell® extender respectively. The C.R. recorded for TEYG was 53.20% while in Bioxcell® extender it was 52.67%. It is inferred that Bioxcell® can be alternatively used for cryopreservation of bull semen with comparable post thaw sperm parameters with that of TEYG extender.